Multi‐Event Study of Simultaneous Observations of Isolated Proton Auroras at Subauroral Latitudes Using Ground All‐Sky Imagers and the Van Allen Probes. Issue 9 (13th September 2022) - Nakamura, Kohki; Shiokawa, Kazuo; Nosé, Masahito; Nagatsuma, Tsutomu; Sakaguchi, Kaori; Spence, Harlan; Reeves, Geoff; Funsten, Herbert O.; MacDowall, Robert; Smith, Charles; Wygant, John; Bonnell, John; et al.
Abstract: Isolated proton auroras (IPAs) appearing at subauroral latitudes are generated by energetic protons precipitating from the magnetosphere through interaction with electromagnetic ion cyclotron (EMIC) waves. Thus, an IPA is the ionospheric projection of the spatial and temporal variation of wave‐particle interaction regions in the magnetosphere. In this study, we conducted unique multi‐event analysis of simultaneous observations of IPAs and their source regions on 22 April, 7 September, and 22 March 2018, using all‐sky imagers at subauroral latitudes and the Van Allen Probes. When the satellite footprint passed over the IPAs associated with ground Pc1 geomagnetic pulsations, locally generated He + ‐band EMIC waves with the same frequencies as the ground Pc1 pulsations were observed in all events. The IPAs and EMIC waves had comparable narrow widths in the latitudinal direction. The EMIC waves appeared during the rapid enhancement of the ring current proton flux at energy range of ∼10–50 keV, while they disappeared at the rapid decrease of the electron density. From these results, we conclude that the boundaries of the localized IPAs and EMIC waves were determined by the overlap region of energetic proton enhancement and the plasmasphere. This overlap of ring‐current protons and plasmasphere is a favorable condition for the pitch‐angle scattering of protons by the EMIC waves. Characteristic magnetic and electric field variations with the IPAs were not observed by the satellite, indicating that the IPAs were not accompanied by field‐aligned currents comparable to that of oval auroral arcs. Plain Language Summary: Isolated proton auroras (IPAs) appearing at subauroral latitudes (∼55–65°) are generated by energetic protons precipitating from the Earth's magnetosphere, possibly through interaction with plasma waves, that is, electromagnetic ion cyclotron (EMIC) waves. An IPA indicates the spatial and temporal variation of wave‐particle interaction regions in the magnetosphere. EMIC waves are expected to contribute to the rapid loss of radiation‐belt particles into the atmosphere and affect human activities in space. In this study, we report unique multi‐event analysis of simultaneous observations of IPAs and their source regions, using all‐sky imagers at subauroral latitudes and the Van Allen Probes on 22 April, 7 September, and 22 March 2018. When the satellite footprint passed over the IPAs, locally generated EMIC waves were observed in all events. The IPAs and EMIC waves had comparable narrow widths in the latitudinal direction. These results indicate that the IPAs were caused by the EMIC waves. The appearance and disappearance of the EMIC waves were correlated with the rapid enhancement of energetic proton flux and the rapid decrease of the local electron density, respectively. We conclude that the boundaries of the localized IPAs and EMIC waves were determined by the overlap region of energetic proton enhancement and the plasmasphere. Key Points: Three ground‐satellite conjugate observations of isolated proton auroras (IPAs) and their magnetospheric source regions are reported Van Allen Probes observed electromagnetic ion cyclotron (EMIC) waves which had radial ranges corresponding to latitudinal widths of IPAs in the ionosphere in all events We conclude that the IPAs and EMIC waves are excited in the region where enhanced ring current flux overlapped with stable plasmasphere